ASSESSING PHOTORECEPTOR STRUCTURE AFTER MACULAR HOLE CLOSURE. Issue Volume 9:Issues 1(2015:Winter) (2015) - Hansen, Sean; Batson, Sean; Weinlander, Kenneth M.; Cooper, Robert F.; Scoles, Drew H.; Karth, Peter A.; Weinberg, David V.; Dubra, Alfredo; Kim, Judy E.; Carroll, Joseph; Wirostko, William J.
Abstract : Purpose: To describe photoreceptor structure and recovery after macular hole (MH) closure with pars plana vitrectomy (PPV) using adaptive optics scanning light ophthalmoscopy and spectral domain optical coherence tomography. Methods: A pilot imaging study of four eyes from four subjects undergoing PPV for MH was conducted. Imaging with spectral domain optical coherence tomography and adaptive optics scanning light ophthalmoscopy was performed at varying time points after PPV. Results: Despite successful MH closure, disruption of the foveal inner segment ellipsoid zone was seen in all patients when imaged at a mean of 117 days after PPV. Disruption of the photoreceptor mosaic was seen using adaptive optics scanning light ophthalmoscopy at locations corresponding to regions of ellipsoid zone disruption on spectral domain optical coherence tomography. Cone density immediately surrounding these disruptions was normal, except for one patient. In 2 patients who were imaged serially up to 516 days after PPV, recovery of cone cells within regions of mosaic disruption could be detected over time. Conclusion: Photoreceptor disruption exists even after apparent MH closure. Remodeling of the foveal cone mosaic continues for many months after surgery, perhaps accounting for the delayed postoperative improvements of visual acuity in some patients. Spectral domain optical coherence tomography and adaptive optics scanning light ophthalmoscopy are useful tools for monitoring photoreceptor recovery after surgical closure of MH. Abstract : Supplemental Digital Content is Available in the Text.Adaptive optics scanning light ophthalmoscopy is a valuable tool for evaluating photoreceptor structure and recovery after surgical closure of macular hole. It demonstrates persistent disruption of the photoreceptor mosaic with subsequent remodeling for months after surgery, perhaps accounting for the delayed postoperative improvements of visual acuity in some patients.